Respostas
respondido por:
9
Antes temos que determinar o número de termos.( n )
Fórmula: an = a1 + (n - 1).r
an = 84
a1 = -16
n = ??
r = 2
84 = -16 + (n - 1).2
84 = -16 + 2n - 2
84 + 18 = 2n
102 = 2n
n = 102/2
n = 51
Agora aplicamos a fórmula da soma da PA:
Sn = (a1 + an).n/2
Sn = (-16 + 84).51/2
Sn = 68.51/2
Sn = 3468/2
Sn = 1734
★Espero ter ajudado! tmj
Fórmula: an = a1 + (n - 1).r
an = 84
a1 = -16
n = ??
r = 2
84 = -16 + (n - 1).2
84 = -16 + 2n - 2
84 + 18 = 2n
102 = 2n
n = 102/2
n = 51
Agora aplicamos a fórmula da soma da PA:
Sn = (a1 + an).n/2
Sn = (-16 + 84).51/2
Sn = 68.51/2
Sn = 3468/2
Sn = 1734
★Espero ter ajudado! tmj
respondido por:
4
An = A1 + (n-1) . r
84 + 16 = (n-1) . 2
100/2 = n-1
51 = n
S51 = (-16 + 84). 51 /2
S51 = 68 . 51/2
S51 = 1734
84 + 16 = (n-1) . 2
100/2 = n-1
51 = n
S51 = (-16 + 84). 51 /2
S51 = 68 . 51/2
S51 = 1734
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás